Dietary diversity contributes to delay biological aging - Liao, Wen; Li, Meng-ying (Frontiers in Medicine, 2024)
Aims As aging is a major risk factor for chronic diseases, strategies to promote healthy aging are essential. Dietary diversity has been reported to be beneficial for human health, however, the role in the biological aging process remains underexplored. Our aim was to analyse the potential link between diet diversity and aging. Methods Twenty-two thousand six hundred participants from the National Health and Nutrition Examination Survey (NHANES) were included in this study. Dietary diversity was assessed by the dietary diversity score (DDS), which aggregated data on participants’ self-reported dietary categories for the 5 major food groups (18 subgroups) over 2 rounds. Biological age was determined using the phenotypic age, with the residual between biological age and chronological age, phenotypic age acceleration, representing biological aging advance. Weighted multivariate regressions analysis were used to examine the relationship between DDS and phenotypic age acceleration. Sensitivity, subgroup interaction and mediation analyses were employed for further analysis. Results Higher DDS was consistently associated with slower phenotypic age acceleration (β < 0, p < 0.001). Subgroup analyses revealed that the inverse relationship persisted across categories, with minimal interaction effects. Sensitivity analyses confirmed the robustness of results. The oxidative stress indicator glutamyltransferase partially mediated the relationship between DDS and aging [4.9% (3.6, 6.0%), p < 0.001]. Conclusion Dietary diversity is associated with a slower rate of biological aging, which may be due in part to reduced oxidative stress. These findings underscore the potential of a rich, broad-spectrum diet to promote healthy aging and reduce the burden of age-related diseases.